2010
DOI: 10.1002/jsfa.4194
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein-okra polysaccharide fraction blend edible films: tensile properties, water vapor permeability and oxygen permeability

Abstract: BACKGROUND: A hot-buffer-soluble-solid fraction (HBSS) and an alkaline-soluble-solid fraction (ASS) of okra polysaccharides (OKP) were obtained using sequential extraction. These fractions were combined with whey protein isolate (WPI) and glycerol (Gly) plasticizer to form blend edible films. Effects of OKP fraction and content on tensile properties, water vapor permeability (WVP) and oxygen permeability (OP) were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 26 publications
(43 reference statements)
1
18
0
3
Order By: Relevance
“…With regard to EB (Table 4), the CM25 film exhibited a particularly low value, which was reduced by a factor of at least 10 relative to CM50 and CM75 films. The EB values for CM50 and CM75 films were in the range reported in the literature for Opuntia ficus-indica L. mucilage-based films (Espino-Díaz et al, 2010), but were lower than the reported values for whey protein concentrate and CM composite films , whey protein and okra polysaccharide fraction composite films (Prommakool et al, 2011), kefiran-based films (Ghasemlou et al, 2011), and cellophane and LDPE (Smith, 1986).…”
Section: Mechanical Propertiesmentioning
confidence: 50%
“…With regard to EB (Table 4), the CM25 film exhibited a particularly low value, which was reduced by a factor of at least 10 relative to CM50 and CM75 films. The EB values for CM50 and CM75 films were in the range reported in the literature for Opuntia ficus-indica L. mucilage-based films (Espino-Díaz et al, 2010), but were lower than the reported values for whey protein concentrate and CM composite films , whey protein and okra polysaccharide fraction composite films (Prommakool et al, 2011), kefiran-based films (Ghasemlou et al, 2011), and cellophane and LDPE (Smith, 1986).…”
Section: Mechanical Propertiesmentioning
confidence: 50%
“…Oxygen transmission rate value of the PLA/nano‐Ag composite film was measured by an X‐5250I oxygen permeability tester (OxySense Instruments Co, Ltd, Dallas, TX, USA) according to the ASTM standard method D3985. OTR was determined at 20 ± 1°C, 50 ± 1% relative humidity, and 1‐atm pressure difference between the two sides of the film samples . The film was made in a round shape with a diameter of 30 mm.…”
Section: Methodsmentioning
confidence: 99%
“…They are considered to be a stomachic stimulant, antispasmodic, and nervine [1]. Okra seeds have been used on a small scale for oil production.…”
Section: Introductionmentioning
confidence: 99%